Glucosylglycerate Phosphorylase, an Enzyme with Novel Specificity Involved in Compatible Solute Metabolism - Franceus, Jorick (Appl Environ Microbiol, 2017)
Family GH13_18 of the carbohydrate-active enzyme database consists of retaining glycoside phosphorylases that have attracted interest with their potential for synthesizing valuable α-sugars and glucosides. Sucrose phosphorylase was believed to be the only enzyme with specificity in this subfamily for many years, but recent work revealed an enzyme with a different function and hinted at an even broader diversity that is left to discover. In this study, a putative sucrose phosphorylase from Meiothermus silvanus that resides in a previously unexplored branch of the family's phylogenetic tree was expressed and characterized. Unexpectedly, no activity on sucrose was observed. Guided by a thorough inspection of the genomic landscape surrounding other genes in the branch, the enzyme was found to be a glucosylglycerate phosphorylase, with a specificity never before reported. Homology modeling, docking, and mutagenesis pinpointed particular acceptor site residues (Asn275 and Glu383) involved in the binding of glycerate. Various organisms known to synthesize and accumulate glucosylglycerate as a compatible solute possess a putative glucosylglycerate phosphorylase gene, indicating that the phosphorylase may be a regulator of its intracellular levels. Moreover, homologs of this novel enzyme appear to be distributed among diverse bacterial phyla, a finding which suggests that many more organisms may be capable of assimilating or synthesizing glucosylglycerate than previously assumed. IMPORTANCE Glycoside phosphorylases are an intriguing group of carbohydrate-active enzymes that have been used for the synthesis of various economically appealing glycosides and sugars, and they are frequently subjected to enzyme engineering to further expand their application potential. The novel specificity discovered in this work broadens the diversity of these phosphorylases and opens up new possibilities for the efficient production of glucosylglycerate, which is a remarkably potent and versatile stabilizer for protein formulations. Finally, it is a new piece of the puzzle of glucosylglycerate metabolism, being the only known enzyme capable of catalyzing the breakdown of glucosylglycerate in numerous bacterial phyla.